The Implementation of Senior High School Work Immersion Program in Selected Public Schools in Negros Occidental - Vecino, Corazon T.; Doromal, Araceli C. (Philippine Social Science Journal, 2020)
Immersion is implemented in different countries all over the world as part of curricular training. Immersion programs started in other countries many years back. However, the Philippines only started three years ago as a program for students’ engagement in employment simulation. Since the start of the program, there were emerging issues in the insufficiency of documents to establish its extent of implementation. Hence, the paper assessed the extent of implementation of senior high school work immersion program in selected public schools in the Division of Negros Occidental during the school year 2019-2020 according to the category of school, school location, and designation of implementer in the areas of Curriculum Implementation and Compliance, Work Immersion Delivery Process, Assessment of Student’s Progress, Supervision of Work Immersion and Implementation, and Administrative Concerns. Likewise, it identifies the challenges encountered by the implementers and their recommendations in the effective implementation of the immersion program.